STRATEGIC INSIGHTS INTO DIGITAL TRANSFORMATION IN BANKING: DRIVERS AND FRAMEWORKS - Taunk, Shilpa Lunawat; Shukla, Abhilasha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Digital transformation and the resulting business model innovation have significantly reshaped consumer expectations and behaviors, challenged traditional businesses, and disrupted various markets. The digital revolution in India’s financial sector is notably altering the landscape, especially in the banking industry where it has become pivotal in managing the majority of funds within the system. In response to the increasing presence of emerging financial technologies (fintech) that pose a potential threat to the banking sector, numerous financial institutions are actively pursuing digital transformation initiatives. This heightened focus on Digital Transformation has sparked considerable interest among both researchers and practitioners. Despite the abundance of literature on the topic, a detailed exploration of the fundamental factors propelling these transformations, particularly the internal and external dynamics within the specific context of the Indian Banking Sector, remains somewhat limited. This study is centered on delving into the nuances of Digital Transformation within Indian banks to uncover and elucidate the primary drivers of digital transformation in the banking sector. As a result, this research endeavors to devise a comprehensive conceptual framework that captures the essence of the internal and external influences shaping this transformative journey in the Indian banking industry.